Contabilidad ambiental: una propuesta basada en los reportes de sostenibilidad en las industrias minera, petrolera y de gas - Tanaka Nakasone, Gustavo (Pontificia Universidad Católica del Perú, 2015)
This paper proposes an environmental accounting system in Peru that will improve the sustainability reporting of Peruvian corporations and have a positive impact on all the stakeholders (communities, stockholders, government, NGOs, etc.). This new environmental  accounting system will allow companies  to properly quantify and  report environmental issues and have a more integral assessment and analysis of all the variables which affect their triple bottom line.Moreover, environmental issues in Peru will be partially solved when companies adhere to accurate measurement rules, timely submission of data, and fulfillment of government regulations. The principle behind the proposal is that accurate measurement, calculation and reporting on pollution levels will improve the ways companies address environmental and social issues, as well as enhance their financial results. This paper focuses on companies of the mining, gas and oil sectors, since they are arguably some of the main contributors to Peru’s GDP, as well as some of the nation’s largest polluters.